Instytucja upomnienia, o której mowa w art. 173 k.k.w. - Stasiak, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Article 173 of the Executive Penal Code provides for the possibility for the con-victed person or the offender to receive a admonition from the probation officer as an alternative to his or her request to the court. In line with the intentions of the propos-ers of this solution, the purpose of the admonition is to discipline the convicted person (offender) to fulfil his or her obligations related to the probation period. In 2018, court superintendents throughout Poland granted more than 7,000 warnings, which means that on average, a court superintendent applies them twice a year. This article discusses the nature of legal warnings, their application and the possibilities of appeal. The article ends with conclusions.
Keywords: upomnienie; kodeks karny wykonawczy; kurator; sąd; postanowienie; zażalenie na decyzję kuratora sądowego